PENGARUH TEKNOLOGI INFORMASI, KEMAMPUAN TEKNIK PEMAKAI, DUKUNGAN MANAJEMEN PUNCAK DAN KOMPLEKSITAS TUGAS TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI - Agustinus Agung Nugroho, Dewi Saptantinah Puji Astuti & Djoko Kristianto (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
The purpose of this study was to analyze the effect of information technology, user technical capabilities, top management support and task complexity on the performance of accounting information systems. This type of research is a survey of employees of PT. PLN (Persero) APJ Surakarta. The research population was 30 people and the whole was used as a research sample with population research techniques. Data collection techniques used questionnaires. Data analysis techniques used multiple linear regression. The results showed that information technology has a positive and significant effect on the performance of the accounting information system at PT. PLN (Persero) APJ Surakarta. User technical capabilities has a significant positive effect on the performance of the accounting information system at PT. PLN (Persero) APJ Surakarta. Top management support has a positive and significant effect on the performance of the accounting information system at PT. PLN (Persero) APJ Surakarta. Task complexity has a positive but not significant effect on the performance of the accounting information system at PT. PLN (Persero) APJ Surakarta. Keywords: information technology, user technical capabilities, top management support, task complexity, accounting information system performance